Bioinspired DNA Nanointerface with Anisotropic Aptamers for Accurate Capture of Circulating Tumor Cells. Issue 19 (9th August 2020) - Qin, Weiwei; Chen, Liang; Wang, Zhiru; Li, Qian; Fan, Chunhai; Wu, Minhao; Zhang, Yuanqing
Abstract: The capture and analysis of circulating tumor cells (CTCs) have provided a non‐invasive entry for cancer diagnosis and disease monitoring. Despite recent development in affinity‐based CTCs isolation, it remains challenging to achieve efficient capture toward CTCs with dynamic surface expression. Enlightened by the synergistic effect insideimmune synapses, the development of a nanointerface engineered with topology‐defined anisotropic aptamers programmed by DNA scaffold (DNA nanosynapse), for accurate CTCs isolation, is herein reported. As compared to isotropic aptamers, the DNA nanosynapse exhibits enhanced anchoring on the cell membrane with both high and low epithelial cell adhesion molecule (EpCAM) expression. This nanointerface enables accurate capture toward CTCs of heterogeneous EpCAM, without dramatically proportional change inside the mixture of diverse phenotypes. By applying this nanoplatform, CTCs detection as well as downstream analysis for measuring disease status can be achieved in clinical samples from breast cancer patients. Abstract : Inspired by the synergistic effect inside immune synapses, a nanointerface engineered with topology‐defined anisotropic aptamers programmed by DNA scaffold is developed through thermal annealing. Such a nanointerface enables enhanced membrane anchoring and accurate capture toward CTCs of heterogeneous EpCAM, without dramatically proportional change inside the mixture of diverse phenotypes. This nanoplatform can be applied for CTCs detection in clinical samples.